Inside a general election campaign: gender treatment in communications strategy of a female candidate for governor - Glasscock, Joyce Heritage (Kansas State University, 2023)
For decades, researchers studied the communications strategies of political candidates and, specifically, how women candidates manage their campaign communications relative to gender, with feminine approaches believed to impair their chances for success. This study applied framing theory and Functional Theory of Political Campaign Discourse (Functional Theory) to analyze political communications in the 2022 general election campaign for Kansas governor between incumbent Democrat Laura Kelly and Republican Derek Schmidt and how their campaign communications reflected feminine and masculine traits and issues. Findings indicate that Kelly used a mix of feminine and masculine traits to maximize her campaign communications to voters; and her opponent regularly issued attacks in an effort to undermine Kelly’s traits and issue positions considered by voters as critical for executive leadership. The study undertook two approaches to gathering materials for research. First, a quantitative content analysis was conducted to assess the presence of gendered issues and traits in general election campaign communications of tweets, TV ads, and debate statements of Kelly. Then Schmidt’s communications using the same platforms were examined for presence of acclaims, attacks, and defenses, with particular attention to Schmidt’s attacks of Kelly’s traits and issues relative to gender. Similar treatment occurred for TV ads sponsored by major political parties and leading political action committees in support of the candidates. Materials collected for these analyses were from the general election campaign in Kansas, beginning in early August and ending on election day, November 8, 2022. Second, qualitative research was conducted involving interviews during the general election campaign with the governor and during and after the campaign with Kelly’s campaign staff. While the election was ongoing and the outcome of the election was yet unknown, interviews with the candidate explored how she viewed gendered issues and traits, as well as treatment of her by her opponent. From these contacts and interviews, the author witnessed the campaign execute on communications strategies in response to the polling environment and to attacks made by Kelly’s opponent. Findings could recommend communications strategies useful in future female versus male political matchups. The current research contributes to Functional Theory as it used the model for examining gendered treatment of attacks against a female candidate in a state governor’s race. The research contributes to framing theory by examining how candidates applied gendered treatment in political communications across multiple platforms, specifically in a female-male gubernatorial matchup. Finally, the findings contribute to the literature that describes gendered traits in communications.
Keywords: Campaign; Framing; Functional theory; Gender; Twitter